Pengaruh Media Sosial Dalam Meningkatkan Brand Awareness “Somethinc” Pada Pengguna Instagram - Chelsea Priscila Andata; Iflah; Kurnia; Sekartaji Anisa Putri (LPPM Universitas Bina Sarana Informatika, 2022)
Competition between business actors is increasingly selective and requires a strong strategy in order to build company brand awareness which is one of the goal of Public Relations. One way of marketing that PR does use social media Instagram is called Marketing Public Relations. Skincare products in Indonesia are growing at home and abroad. One of the skin care products is Somethinc. Several efforts as a form of existence to increase brand awareness can be seen in marketing through social media run by the company in order to be able to compete with other brands. This study aims to determine and analyze the influence of social media to increasing brand awareness. This research method uses quantitative methods with descriptive and causal research types. This research uses the Lemeshow formula and purposive sampling technique. The sample in this study amounted to 100 respondents. The data analysis technique used is descriptive analysis and simple linear regression analysis. The data analysis of this research used SPSS with 16 statements from both variables. The data obtained states that are aged above 15 years old, and know about skincare Somethinc. The results of this study indicate that the Instagram social media variable has a positively affect on increasing brand awareness of the Somethinc skincare brand on Instagram social media users. Instagram social media is effectively used to increase brand awareness of Somethinc skin care products